Pengaruh Motivasi Kerja, Lingkungan Kerja, dan Budaya Kerja Terhadap Kinerja Karyawan Hotel Khalisma - Putri, Dina Septiani; Tarmizi, Achmad (Prisani Cendekia, 2024)
This research aims to evaluate the influence of work motivation, work environment and work culture on employee performance at the Khalisma Hotel. The research method used is quantitative with a research design using a questionnaire as a data collection tool. The research population was 40 employees from various divisions at the Khalisma Hotel, with sampling carried out in a saturated manner. Data were analyzed using descriptive statistical tests, validity tests, reliability tests, normality tests, multiple linear regression analysis, F tests, and coefficient of determination. The research results show that work motivation has a positive and significant influence on employee performance. However, the work environment and work culture do not have a significant effect on employee performance. These findings indicate that employee enthusiasm and internal encouragement play a more important role in improving performance than work environment factors and organizational culture.